Pembuatan Pupuk Organik Cair Pembenah Tanah dari Lindi dan Aplikasinya Pada Tanaman Cabai, Tomat, Terong - Bahri, Syaiful; Ambarwati, Yuli; Rinawati, Rinawati; Widiarto, Sony; Hardiyanto, Candra (Jurnal Kartika Kimia, 2025)
Liquid organic fertilizer is a solution from the decay of organic materials whose basic ingredients come from animals or plants that have undergone fermentation. This research aims to process traditional market organic waste with the addition of biang which can produce a product in the form of liquid organic fertilizer derived from the combination of biang and leachate. In this research, soil improver liquid organic fertilizer samples were tested and according to a ministerial degree of Agriculture of the Republic of Indonesia No. 261 of 2019 concerning Organic Fertilizers, Biofertilizers and Soil Improvement. Applications were made on topsoil, subsoil 1, and subsoil 2 containing chili, tomato, and eggplant plants and plant height observations were made for 30 days. Laboratory tests of liquid organic fertilizer for soil improvement, the results obtained only the parameters of heavy metals, pH, C-organic and micronutrients (Fe) that have met the quality standards. The results of plant height observations obtained a significant increase in plant growth and the application of liquid organic fertilizer soil improver can make subsoil soil compete with topsoil soil. Further research needs to be done by utilizing other alternative materials to increase the levels of macro and micronutrients and so that the results obtained can meet the quality standards used.